Reflective Abstraction of Students of Middle School with Disabilities in Solving Mathematical Problems - Isnaini, Farida; Putra, Eric Dwi; Lutfiyah, Lutfiyah (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The ability to identify, reflect, and generalize mathematical concepts from previous learning experiences into new situations is known as reflective abstraction. This study intends to examine the reflective abstraction process carried out by students with disabilities in solving mathematical problems. This research is a qualitative study that employs a descriptive approach. This study involved two students with hearing impairments who were purposively selected at the middle school level in Branjangan, Jember. Data were collected through observations, interviews, and supporting documents related to the mathematical problem-solving process. The results of the study show that this reflective abstraction process varies depending on the type of disability and the students' learning experiences. Factors such as teacher support, the use of visual aids, and previous learning experiences play a significant role in student success. This study offers explanations for how students with disabilities develop their understanding and highlights the importance of adaptive and inclusive learning approaches to support them. We hope that these findings will serve as a foundation for the creation of more inclusive learning strategies, especially in teaching.